Barbara Maher; Cakes - D., J.M. (Petits Propos Culinaires, 2025)
Barbara Maher; Cakes: Jill Norman & Hobhouse, London, 1982: 398 pp., black and white illustrations by Soun, some colour photographs by Christine Hanscomb, bibliography, index. £7.95.